Leaf tobacco : its contribution to the economic and social development of the Third World - Economist Intelligence Unit (Great Britain) (London : Economic Intelligence Unit (EIU), 1980)
The publication examines the contribution of tobacco leaf to the economic and social development of the Third World
Accompanied by an outline.
lje 28/06/2017
Loans
Keywords: Tobacco industry; Developing countries